Progression of Kidney Disease in Kidney Transplant Recipients With a Failing Graft: A Matched Cohort Study - Ngan N. Lam; Robert R. Quinn; Alix Clarke; Huda Al-Wahsh; Greg A. Knoll; Lee Anne Tibbles; Fareed Kamar; Rachel Jeong; James Kiberd; Pietro Ravani (Canadian Journal of Kidney Health and Disease, 2023)
Background: Few studies have assessed outcomes in transplant recipients with failing grafts as most studies have focused on outcomes after graft loss. Objective: To determine whether renal function declines faster in kidney transplant recipients with a failing graft than in people with chronic kidney disease of their native kidneys. Design: Retrospective cohort study. Setting: Alberta, Canada (2002-2019). Patients: We identified kidney transplant recipients with a failing graft (2 estimated glomerular filtration rate [eGFR] measurements 15-30 mL/min/1.73 m 2 ≥90 days apart). Measurements: We compared the change in eGFR over time (eGFR with 95% confidence limits, LCL eGFR UCL ) and the competing risks of kidney failure and death (cause-specific hazard ratios [HRs], LCL HR UCL ). Methods: Recipients (n = 575) were compared with propensity-score-matched, nontransplant controls (n = 575) with a similar degree of kidney dysfunction. Results: The median potential follow-up time was 7.8 years (interquartile range, 3.6-12.1). The hazards for kidney failure (HR 1.10 1.33 1.60 ) and death (HR 1.21 1.59 2.07 ) were significantly higher for recipients, while the eGFR decline over time was similar (recipients vs controls: –2.60 –2.27 –1.94 vs –2.52 –2.21 –1.90 mL/min/1.73 m 2 per year). The rate of eGFR decline was associated with kidney failure but not death. Limitations: This was a retrospective, observational study, and there is a risk of bias due to residual confounding. Conclusions: Although eGFR declines at a similar rate in transplant recipients as in nontransplant controls, recipients have a higher risk of kidney failure and death. Studies are needed to identify preventive measures to improve outcomes in transplant recipients with a failing graft.